Optimal colorectal cancer screening in states' low-income, uninsured populations - The case of South Carolina - Van Der Steen, A.; Knudsen, A.; Van Hees, F.; Walter, G.; Berger, F.; Daguise, V.; Kuntz, K.; Zauber, A.; Van Ballegooijen, M.; Lansdorp_Vogelaar, Iris (Blackwell Publishing Inc., 2015)
© Health Research and Educational Trust.Objective To determine whether, given a limited budget, a state's low-income uninsured population would have greater benefit from a colorectal cancer (CRC) screening program using colonoscopy or fecal immunochemical testing (FIT). Data Sources/Study Setting South Carolina's low-income, uninsured population. Study Design Comparative effectiveness analysis using microsimulation modeling to estimate the number of individuals screened, CRC cases prevented, CRC deaths prevented, and life-years gained from a screening program using colonoscopy versus a program using annual FIT in South Carolina's low-income, uninsured population. This analysis assumed an annual budget of $1 million and a budget availability of 2 years as a base case. Principal Findings The annual FIT screening program resulted in nearly eight times more individuals being screened, and more important, approximately four times as many CRC deaths prevented and life-years gained than the colonoscopy screening program. Our results were robust for assumptions concerning economic perspective and the target population, and they may therefore be generalized to other states and populations. Conclusions A FIT screening program will prevent more CRC deaths than a colonoscopy-based program when a state's budget for CRC screening supports screening of only a fraction of the target population.